Respuesta :

Answer:

Given equation:  y = x² + 2x - 3

If you wish to find the values of y when x = -2 and x = -5:

When x = -2:

⇒ y = (-2)² + 2(-2) - 3

⇒ y = 4 - 4 - 3

⇒ y = -3

When x = -5:

⇒ y = (-5)² + 2(-5) - 3

⇒ y = 25 - 10 - 3

⇒ y = 12

If you wish to find the value of y when x = -2-5:

When x = -2-5 ⇒ x = -7

⇒ y = (-7)² + 2(-7) - 3

⇒ y = 49 - 14 - 3

⇒ y = 32

Answer:

y = 32

Step-by-step explanation:

Given :-

y = x² + 2x - 3

x = -2-5 = -7

To Find :-

y

Inputting the value of x :

y = (-7)² + 2(-7) - 3

y = 49 - 17

Solution :-

y = 32